Application of frequency extension processing technology in logging constrained inversion. Issue 1 (September 2021) - Huang, Yi; Luo, Ming; Li, Wentuo; Xiao, Ping; Guo, Wei; Shu, Mengcheng; Cheng, Sen
Abstract: The resolution of seismic data affects the accuracy of sand body identification. Generally, the higher the resolution of seismic data, the higher the accuracy of sand body identification. Aiming at the problem of low seismic resolution in block X, this paper attempts to increase the effective signal bandwidth of the original seismic data by using the frequency extension method, maximize the resolution on the premise of ensuring that the seismic data are not distorted, and then use the waveform indication inversion technology to predict the reservoir after the frequency extension. Compared with the drilled wells, it is found that the combination of frequency extension and waveform indication inversion can not only improve the vertical resolution of seismic data, but also maintain the lateral continuity of seismic data, which conforms to the distribution characteristics of sand body and has higher prediction accuracy. The method of frequency extension + waveform indication inversion has a good application prospect, which provides a new idea for the next step of sand body characterization and well location deployment.